2012
DOI: 10.1007/s00264-012-1670-y
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the talonavicular joint using angle-stable mini-plates: a prospective study

Abstract: For the treatment of talonavicular arthritis, the application of mono- and multidirectional angle-stable mini-plates provided a strong fixation that led to high union rates and good to excellent overall outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…In order to support consolidation, some authors have used corticospongious iliac bone grafting and plate fixation [25]. Other authors have used a platelet gel concentrate that is placed at the time of soft tissue closure [3].…”
Section: Discussionmentioning
confidence: 99%
“…In order to support consolidation, some authors have used corticospongious iliac bone grafting and plate fixation [25]. Other authors have used a platelet gel concentrate that is placed at the time of soft tissue closure [3].…”
Section: Discussionmentioning
confidence: 99%
“…All patients were reported to obtain significant pain relief and improved overall function according to VAS score. Lechler P et al [4] systematically reviewed that 125 combined cases of isolated TNA have variable results, with rates of complications ranging from 10 to 37.5%; the overall complication rates were 20.8%, including nonunion, adjacent arthritis and hardware-related problems. Barkatali BM and Munoz MA et al [15] reported the nonunion rates of TNA were up to 3.8 ~ 11% and the operation was difficult to obtain satisfactory fusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported that the nonunion rates of TNA were 3.8 ~ 11% [15]. In most cases, the nonunion rates arise from hardware loosening with loss of interface compression and stability function during the healing process [2, 4, 68]. The implants mainly include staples, plates, and screws.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die in der Literatur angegebenen sowie eigene Daten zeigen mehrheitlich gute bis sehr gute Ergebnisse [17,10,18]. Primär steht bei entsprechender Symptomatik die konservative Therapie im Vordergrund.…”
Section: Diskussionunclassified